Estrés académico y el desarrollo de conductas disruptivas en estudiantes de la Unidad Educativa Replica Eugenio Espejo - Romero Arreaga, Iris Vanessa (2025)
The study frames the issue of academic stress and the development of disruptive behaviors in students of the Eugenio Espejo Replica Educational Unit during the 2024-2025 school year. It highlights the importance of understanding the impact of academic stress on the behavior of adolescents and its influence on the academic environment, benefiting students, teachers and parents through the generation of strategies to improve the educational dynamics. The methodological design is correlational and non-experimental, using techniques such as an observation form and psychometric tests (Academic Stress Scale EEA-SC18 and Disruptive Behavior Test) applied to a sample of 112 students selected through probabilistic sampling. The results showed that factors such as family pressure, nervousness before exposures and other school demands generate high levels of stress, which in turn is related to disruptive behaviors such as interruptions, talking without permission and resistance to follow rules. It is concluded that academic stress, in its cognitive, emotional and behavioral dimensions, has a significant impact on the development of disruptive behaviors, affecting academic performance and school coexistence. Finally, the need to implement effective coping strategies that promote the emotional and academic well-being of students is highlighted.